O programa mais educação: concepções e desafios para a gestão escolar - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2016)
The dissertation did analysis about the conceptions and practices of integral education and its implications in the actions of the managers of schools that developed the More Education Program of the Santarém / PA Municipal Teaching Network, having as a temporal range the period between the years of 2009 to 2015. The research was developed in three schools, involving six managers, chosen from previously defined criteria. To make a collect of informations it was used as a tool, the semi-structured interview. The informations treatment was carried out using the content analysis technique of Bardin (2011), having as analytical categories: Conceptions of Integral Education and Management Practices. The theoretical referencial used, part from of Saviani's studies (2008, 2014); Cavaliere (2002, 2010); Coelho (2003, 2009); Lück (2012), Bravo (2014), Paro (2009, 2015), Colares (2012). The results found in the present study highlight two antagonistic conceptions in the current context of integral education. The Liberal-Pragmatist Conception, inspired by the pragmatism of John Dewey and Anísio Teixeira, which bases the proposal of the More Education Program and the Marxist Socialist Conception that defends the omnilateral and polytechnical formation and proposes to the historical-critical Pedagogy a theoretical formulation that aims to articulate theory and Practice, mediated by education. The analysis of the speeches shows that the school managers have little or no clarity about the conceptions of integral education that guide their practices, besides revealing little knowledge about the theoretical foundations that guide the More Education Program. Participatory management practices present advances such as the construction of the Political-Pedagogical Project and the participation of the school council. However, participatory processes do not include the whole school community. It is noticed the growing of participation of parents and community, but students are excluded from planning and of the school management decisions. The research demonstrates the needness latent to establish debate in school spaces on integral education and democratic management practices, with the perspective of an emancipatory education for schools in the Amazon.
Keywords: Educação Integral; Programa Mais Educação; Gestão Escolar; Educação -- Amazônia; CNPQ::CIÊNCIAS HUMANAS::EDUCAÇÃO SUPERIOR:: GESTÃO EDUCACIONAL; HISTÓRIA, POLÍTICA E GESTÃO EDUCACIONAL NA AMAZÔNIA; HISTÓRIA, POLÍTICA E GESTÃO EDUCACIONAL NA AMAZÔNIA